2009
DOI: 10.1002/j.2050-0416.2009.tb00370.x
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of β-amylase Activity and Protein Fractions in Barley Grains as Affected by Genotypes and Post-anthesis Temperatures

Abstract: The variation of β-amylase activity and protein fractions in barley grains was evaluated using 148 barley genotypes grown in the field and two cultivars under in vitro culture with two temperature treatments during grain development. The results showed that there was significant genotypic variation in β-amylase activity and protein fraction content. Regression analysis indicated that β-amylase activity was positively correlated with total protein and the level of each of the protein fractions, with the correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
3
13
0
3
Order By: Relevance
“…The observed β-amylase activity in the selected accessions agreed with previous research which suggested a range of β-amylase activity in Chinese landraces from 93 to 2372 U g –1 [12]. Compared with β-amylase activity in Adorra-like, Haruna Nijo-like and PI296897-like cultivars [22], the lowest β-amylase activity observed in z043 was higher than Adorra-like cultivars and the β-amylase activity of m279, L35 and L47 was similar to Haruna Nijo.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed β-amylase activity in the selected accessions agreed with previous research which suggested a range of β-amylase activity in Chinese landraces from 93 to 2372 U g –1 [12]. Compared with β-amylase activity in Adorra-like, Haruna Nijo-like and PI296897-like cultivars [22], the lowest β-amylase activity observed in z043 was higher than Adorra-like cultivars and the β-amylase activity of m279, L35 and L47 was similar to Haruna Nijo.…”
Section: Discussionsupporting
confidence: 90%
“…The Qinghai-Tibetan plateau has been suggested as the centre of origin for Chinese landraces [10]. However, to date, the knowledge of the Chinese barley germplasm gene pool has been restricted to differences between Chinese landraces and Tibetan wild barley in some traits, such as salt tolerance [11] and protein content [12]. There is no comprehensive research on the genetic variation of malting quality traits [13].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the weather during the grain filling stage, 2012 had lower temperatures and more rainfall than 2009. In a previous study, we found that high temperatures during the filling stage could cause higher BAA (Wei et al, 2009b). The current results suggest that BAT varies in relation to temperature and rainfall.…”
Section: Discussionsupporting
confidence: 70%
“…The aim of malting is to achieve adequate endosperm modification to generate the desired malt quality, which, besides the process, depends on genotype and environmental conditions during the barley growing season (Molina-Cano et al, 1995;Molin-Cano et al, 1997). It has been noticed that factors like temperature and excessive nitrogen application for barley management affect protein levels, mainly hordeins (Qi et al, 2006;Wei et al, 2009). condiciones ambientales presentes durante el desarrollo del cultivo de cebada (Molina-Cano et al, 1995;Molina-Cano et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…condiciones ambientales presentes durante el desarrollo del cultivo de cebada (Molina-Cano et al, 1995;Molina-Cano et al, 1997). Se ha observado que diferentes factores como temperatura y la excesiva aplicación de nitrógeno durante el manejo de este cultivo afectan los niveles de proteína, principalmente hordeínas (Qi et al, 2006;Wei et al, 2009).…”
Section: Introductionunclassified